2017
DOI: 10.1093/cercor/bhw405
|View full text |Cite
|
Sign up to set email alerts
|

Axotomized Corticospinal Neurons Increase Supra-Lesional Innervation and Remain Crucial for Skilled Reaching after Bilateral Pyramidotomy

Abstract: Skilled upper limb function heavily depends on the corticospinal tract. After bilateral lesions to this tract, motor control is disrupted but can be partially substituted by other motor systems to allow functional recovery. However, the remaining roles of motor cortex and especially of axotomized corticospinal neurons (CSNs) are not well understood. Using the single pellet retrieval task in adult rats, we induced significant recovery of skilled reaching after bilateral pyramidotomy by rehabilitative reaching t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 82 publications
0
18
0
Order By: Relevance
“…There is still incomplete understanding of the precise role played by brainstem-descending pathways in motor recovery from lesion, as well as by corticobulbar pathways. Although previous reports speculated that corticobulbar projections may play an important role in motor recovery after lesion of the CNS (Beaud et al, 2008;Hoogewoud et al, 2013;Mosberger et al, 2017;Wyss et al, 2013;Zörner & Schwab, 2010), this descending tract still remains mysterious for the most part, possibly due in part to its location and the difficult access to the corresponding target nuclei in the brainstem. The present study is original as it represents a unique study in nonhuman primates quantitatively investigating the rearrangement of the corticobulbar projections onto the PMRF following different pathologies affecting the CNS, such as motor cortex lesion, PD or SCI.…”
Section: Functional Significancementioning
confidence: 99%
“…There is still incomplete understanding of the precise role played by brainstem-descending pathways in motor recovery from lesion, as well as by corticobulbar pathways. Although previous reports speculated that corticobulbar projections may play an important role in motor recovery after lesion of the CNS (Beaud et al, 2008;Hoogewoud et al, 2013;Mosberger et al, 2017;Wyss et al, 2013;Zörner & Schwab, 2010), this descending tract still remains mysterious for the most part, possibly due in part to its location and the difficult access to the corresponding target nuclei in the brainstem. The present study is original as it represents a unique study in nonhuman primates quantitatively investigating the rearrangement of the corticobulbar projections onto the PMRF following different pathologies affecting the CNS, such as motor cortex lesion, PD or SCI.…”
Section: Functional Significancementioning
confidence: 99%
“…Preclinical studies have demonstrated significant functional recovery based on neuroplastic changes within both perilesional 5,14 and contralesional cortex, 16 spinal cord, 17,18 and rubrospinal tracts. 19,20 This has led to the view that by utilizing task-specificity principles and focusing treatment on surviving networks and their connections, it will be possible to tailor rehabilitative strategies to maximize poststroke recovery. [21][22][23] Previous investigations have demonstrated the efficacy of combining of environmental enrichment and task-specific reach training to promote poststroke recovery.…”
mentioning
confidence: 99%
“…Studies have largely attributed cortical reorganization in rodents to remodeling of the corticospinal tract or other descending tracts [64,[89][90][91][92][93]. This is due, in part, to the observation that injured, and intact, axons departing the cerebral cortex (corticofugal axons) have been found to elicit new growth coincident with the changes in cortical motor maps.…”
Section: Reorganization Of Motor Cortex After Spinal Cord Injurymentioning
confidence: 99%
“…Alternative pathways for cortical input to the spinal cord exist and even arise as collateral projections from corticospinal neurons. After bilateral transection at the level of the medullary pyramids (pyramidotomy), injured corticospinal axons sprout into the red nucleus, supporting recovery of skilled forelimb function [91]. Chemogenetic silencing of the injured corticospinal neurons, or forelimb motor cortex stroke, disrupts this behavioral recovery [91].…”
Section: Reorganization Of Motor Cortex After Spinal Cord Injurymentioning
confidence: 99%
See 1 more Smart Citation